Morfometria e uso da terra da bacia hidrográfica do Rio do Coco e suas implicações sobre a produção e transporte de sedimentos - Almeida, Rejane Freitas Benevides (2017)
This study aimed to evaluate the influence of morphometric aspects and land use in the areas of permanent preservation of watercourses on the production and transport of sediments in the Rio do Coco watershed. It is located on the right bank of the Araguaia River basin, in the state of Tocantins, between the municipalities of Caseara, Marianópolis do Tocantins, Divinópolis do Tocantins, Monte Santo, Paraíso do Tocantins, Chapada de Areia, Pium and Barrolândia. The first phase of the study consisted of compartmentalization and morphometric analysis of the basin, where it was verified the existence of regions (high basin) with natural characteristics indicative of greater susceptibilities that may potentiate sediment supply, pointing out the need of more effective planning of the use activities. The second phase was dedicated to evaluating the cover and the soil use of the Rio do Coco basin, in addition to identifying and quantifying the percentage of areas with land use conflicts in the areas of permanent preservation of water courses. For this purpose, the mapping of land cover and land use was carried out using images from Landsat 8 (2015) satellite. For the identification of PPAs buffers with buffer strips were created according to the limits defined in the legislation. The conflicts of land use in APP were measured after the overlap of the map generated in the classification and the PPA map, being verified for the entire basin 32.8% of areas with conflicts of use along the bodies of water and, although the sub-basins belonging to the region of the high basin are the regions with greater irregularities. The third and last phase of the thesis evaluated the production and transport of sediments in the Rio do Coco basin and its most representative sub-basins. This analysis was carried out by means of measurements of liquid and solid discharges in the Coco River and in the mouth of the channels of the main sub-basins. Measurements were initiated in November 2014 extending through April 2016 from bimonthly collections. The quantification of the solids load obeyed the methodology defined by Carvalho (2000b), and the flow measurements are performed using the following flow meters: ADV (Acoustic Doppler Velocimeter) FlowTracker and ADCP (Acoustic Doppler Current Profiler). The total discharge followed the method of Colby (1957) in Carvalho (2000a) and the specific production of sediments was analyzed based on the methodology of Carvalho (2008). From these analyzes it was possible to measure the volume of material transported by the main drainage channels of the basin, being proved that the region of the high basin is responsible for most of the sediments produced and transported in the water bodies. It should be noted, therefore, that this material has not arrived fully in the Araguaia River, part is being deposited along the canal, it is evident that in the basin there is an environment where production and transportation predominate and in another the accumulation. The results found in this phase of the research only reinforce the evidence observed in previous phases, where it was verified that the morphometric aspects are determinant in the sedimentological discharge of the basin, being the use and coverage of the soil considered maximizer of the whole process.